IDA AND ON THE TREATMENT OF IDA DNA DAMAGE: 8-HYDROXY-2-DEOXYGUANOSINE LEVEL - Esen, B.; Akarsu, S.; Aydin, S. (Ferrata Storti Foundation, 2015)
[Abstract Not Available]
20th Congress of European-Hematology-Association -- JUN 11-14, 2015 -- Vienna, AUSTRIA